ISLAMIC CRIMINAL LAW ON JARIMAH ZINA'S TESTIMONY: UNCOVERING THE CONFLICTS BETWEEN SHARIA DOCTRINE AND REALITY - Islamul Haq; Marilang; Kurniati (Al-Risalah, 2022)
The purpose of this study was to examine the orientalist N.J. Coulson's point of view on the discrepancy between the doctrine of Sharia and reality in the case of adultery in the evidence of a witness. This research was qualitative in nature and employed a descriptive normative juridical technique to answer the research questions. Documenting data, conducting data analysis through reduction, presenting data and drawing conclusions were all examples of data collection techniques. With regard to the testimony of adultery, the researcher aimed to uncover and then offer evidence regarding the disagreement between Sharia doctrine and reality in order to better understand the phenomenon. Based on the findings of the study, it could be stated that Islamic Sharia is a Sharia that places a great value on human honor, and that hifz al-irdh was one of the maqashid sharia, or honor code. With the introduction of hifz al-'irdh, the Islamic Criminal Law had strengthened the requirement for four witnesses to testify in an adultery case. This was also consistent with the punishment for adultery, which might range from stoning to death. However, the criticism levelled against N.J. Coulson regarding the seeming conflict between Sharia doctrine and reality in terms of the strictness of testimony was essentially incorrect, as Islamic law granted the privilege of maintaining human honor (hifz al-'irdh) rather than a conflict.